The French Socialist Party: Membership between Closed and Open Primaries - Marino De Luca (Coordinamento SIBA, 2015)
For some years now the clamor for democratisation of parties' internal functioning has been spreading across democracies. Among them, France has advanced impressively in the past few years. In 2006, the Socialist Party (PS) launched a closed primary to choose the socialist candidate, Ségolène Royal, for the 2007 presidential election. Approaching the 2012 presidential elections, the leftist coalition (PS and PRG) launched open primary elections to select its chief-executive candidates, with François Hollande finally emerging as a nominee. In this article, we shall examine how the socialist membership changed during the past three socialist congresses, analysing the outcome of the two above-mentioned primary elections. In particular, we shall observe the Le Mans (2005), Reims (2008) and Toulouse (2012) Congresses, and describe membership, participation, and competitiveness within the PS. The study was based on data collected from an administrative unit, the French départements.